Cover, Content, and Editorial Note from J Mol Docking Vol. 1 No. 2 December 2021 - Chief Editor of J Mol Docking (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. After a long wait for almost one year from the first planned, the new scientific journal of the Department of Pharmacy Universitas Muhammadiyah Palangkaraya can be published. This scientifc journal was named Journal of Molecular Docking (J Mol Docking), inspired by one of the most popular in silico methods in computer-aided drug design. Journal of Molecular Docking published every 6 months (2 issues/year) every June and December. This edition contains five articles consisting of writings from six countries including Egypt, Indonesia, Serbia, Slovenia, Bangladesh, and Vietnam. The authors come from several institutions, including Bio Search Research Institution, Sekolah Tinggi Farmasi Muhammadiyah Tangerang, Cairo University, Benemérita Universidad Autónoma de Puebla, Univerzitet u Prištini, Alma Mater Europaea – ECM, Univerzitet Privredna akademija u Novom Sadu, Univerzitet Odbrane, Vojvode Tankosica Health Center, BDORT Center for Functional Supplementation and Integrative Medicine, Jagannath University, Can Tho University, and Universitas 17 Agustus 1945 Jakarta. Editorial boards are fully aware that there are still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repetoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for the the publication in the next edition on June 2022. Wassalamu’alaikum Wr. Wb.